When Opinion Leaders Tweet: Framing Analysis Of Kuwaiti Parliament Members’ Tweets - Salem, Fatima Al (The Turkish Online Journal of Design Art and Communication, 2012)
This research investigated Kuwaiti parliament members’ leadership behavior on Twitter by applying Bolman and Deal’s (1984) leadership theory of framing. The study classified parliament members according to their political party affiliation-Islamists, independents, liberals, and populists party- and investigated the prevalence of four leadership frames through a content analysis of eight parliament members’ messages on Twitter over a period of six months from June 15, 2011 to November 15, 2011. Results showed that, overall, the structural frame was the most commonly used frame among parliament members, followed by the political, symbolic, and human resource frame respectively. The use of frames depended on both the political group and the topic of issues. The Islamist group, liberal and populist party more often used the structural frame in their Twitter messages whereas the independent group more often used the political frame.
Keywords: Opinion Leaders; Fikir Liderleri; Twitter; New Media; Yeni Medya